PAEDIATRIC NEW HIV INFECTIONS IN MALAWI A BOX-JENKINS ARIMA APPROACH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Using annual time series data on the number of children (ages 0 – 14) newly infected with HIV in Malawi from 1990 – 2018, the study predicts the annual number of children who will be newly infected with HIV over the period 2019 – 2030. The paper applies the Box-Jenkins ARIMA methodology. The diagnostic ADF tests show that, S, the series under consideration is an I (2) variable. Based on the AIC, the paper presents the ARIMA (2, 2, 0) model as the optimal model. The diagnostic tests further show that the presented model is stable and its residuals are not serially correlated and are also normally distributed. The results of the study indicate that the number of new HIV infections in children in Malawi will continue to go down over the out-of-sample period. Our model implies that by 2021, Malawi could materialize a society free of pediatric HIV. In this regard, the country could be a good example, especially for neighboring countries; of how pediatric HIV can be prevented and controlled.